Demand for low-cost housing among local people in Perak - Mohamed Osman, Mariana; Shuid, Syafiee; Bachok, Syahriah; Khalid, Najihan (2016)
Housing serves one of basic human needs. Hence housing quality positively relates to human well-being. This paper explores factors influencing housing demand in Perak. ISSUE: In Perak, the housing supply has yet to respond to the increasing housing demand with regards to the rising population. AIM: The aims of this research is to assess the current demand and supply of low-cost housing stock in Perak. METHOD: Content analysis was conducted based on secondary data gathered from government agencies such as National Property Information Centre (NAPIC), Department of Statistics Malaysia and Perak Land and Mineral Office. FINDINGS: According to previous studies, nine factors were influencing the demand for low-cost housing. The factors include (i) population growth, (ii) birth rate, (iii) child mortality rate, (iv) income rate, (v) poverty rate, (vi) unemployment rate, (vii) housing stock (viii) inflation rate, and (ix) Gross Domestic Product (GDP). Recent studies discovered that out of the nine factors, only three of the factors significantly influence the housing demand in Perak. These factors were (i) demographic factors, (ii) monthly household income, and (iv) housing supply. The rate of population growth had drastically increased from the year 2000 to 2010. Additionally, more than 50% of the household in Perak had an average monthly income of less than RM 2,999. Despite these issues, the low-cost housing stock from the year 2010 to 2015 had significantly decreased eventhough the demand for these types of houses was high. The lack of low cost housing units leads to poor well-being as population face (i) burden of high rental, (ii) overcrowding and (iii) substandard housing. Therefore, constant monitoring by the related authorities on the construction of low cost houses is imperatively in need to ensure the continued supply of the low-cost housing targeted to the low-income population.